2017
DOI: 10.1038/srep43737
|View full text |Cite
|
Sign up to set email alerts
|

Dose- and time- effect responses of DNA methylation and histone H3K9 acetylation changes induced by traffic-related air pollution

Abstract: As an important risk factor of respiratory disorders, traffic-related air pollution (TRAP) has caused extensive concerns. Epigenetic change has been considered a link between TRAP and respiratory diseases. However, the exact effects of TRAP on epigenetic changes are still unclear. Here we investigated the dose- and time- effect responses of TRAP on DNA methylations and H3K9 acetylation (H3K9ac) in both blood and lung tissues of rats. The findings showed that every 1 μg/m3 increase of TRAP components were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Meanwhile, results from multiple analyses, including DNA methylation frequency changes (Table ), hierarchical AMOVA (Table ) and shared DNA methylation state of the 2‐408 locus after multiple challenges, clearly showed time‐dependent effects of DNA methylation changes. Time–effect response of DNA methylation was also found in rats exposed to traffic‐related air pollution (Ding et al., ). All these results demonstrate that DNA methylation can rapidly respond to abiotic stresses and timely DNA methylation‐mediated adjustment of functional genes expression can be essential for survival in harsh environments.…”
Section: Discussionmentioning
confidence: 87%
“…Meanwhile, results from multiple analyses, including DNA methylation frequency changes (Table ), hierarchical AMOVA (Table ) and shared DNA methylation state of the 2‐408 locus after multiple challenges, clearly showed time‐dependent effects of DNA methylation changes. Time–effect response of DNA methylation was also found in rats exposed to traffic‐related air pollution (Ding et al., ). All these results demonstrate that DNA methylation can rapidly respond to abiotic stresses and timely DNA methylation‐mediated adjustment of functional genes expression can be essential for survival in harsh environments.…”
Section: Discussionmentioning
confidence: 87%
“…Several studies revealed that the changes of H3K9ac and H3K27ac were associated with air pollution that induced respiratory disorders. 29,30 A previous study conducted by Cui et al . indicated that the acetylation levels of H3K9ac, H3K14ac, H3K27ac, and H3K18ac were obviously elevated in asthmatic lung tissues compared to the control group, 31 which corroborated with our finding.…”
Section: Discussionmentioning
confidence: 98%
“…Given that the histone acetylation is a dynamic and cell-specific process 23 , CD4 + T lymphocytes rather than PBMCs mixture were isolated from peripheral blood in the present study. As a wide range of autoimmune disease 10,24 or subtle stimuli 25 have been found to be associated with epigenetic changes, we enrolled patients with new-onset diabetes without complications and with insulin as the only medication. Covariates including age, sex and body mass index were well matched with controls, allowing for a more accurate determination of the acetylation pattern specific to type 1 diabetes rather than physiological causes.…”
Section: Discussionmentioning
confidence: 99%